Improvement of symptoms in children with autism by TOMATIS training: a cross-sectional and longitudinal study - Fu, Yujia; Tian, Mei; Chen, Jiaxi; Chen, Wenfeng; Li, Huang (Frontiers in Behavioral Neuroscience, 2024)
Autism Spectrum Disorder (ASD) is a neurological condition that is marked by deficits in social interaction, difficulty expressing oneself, lack of enthusiasm, and stereotypical conduct. The TOMATIS training method is an effective music therapy for children with ASD for its individually developed programs to improve behavioral deficits. The research employed both longitudinal and cross-sectional designs. In the cross-sectional study, the experimental group showed significant improvement in symptoms after TOMATIS training compared to the control group of children with ASD. The results validated the effect of TOMATIS treatment for ASD-related deficits, including perceptual-motor, attentional, social, and emotional issues. ASD's auditory hypersensitivity hampers social information processing, but TOMATIS enhances cochlear frequency selectivity, aiding in capturing relevant auditory stimuli. In addition, the longitudinal study confirmed these findings, which proved TOMATIS training effective in clinically treating ASD. This study focused on audiometric indicators and behavioral improvement, elucidating the mechanisms behind the training's success. Behavioral improvements might stem from TOMATIS' frequency selectivity, reshaping auditory organ-cortical feedback loops to filter interference and focus on valid information.